POSITION RESOURCES IN CON CO ISLAND - Thanh, Tran Duc; An, Le Duc; Lan, Tran Dinh; Trang, Trinh Thi Minh; Huyen, Nguyen Thi Minh (Vietnam Journal of Marine Science and Technology, 2017)
Being a basaltic volcano, Con Co island is an isometric hill 2.3 km2 wide and 63 m high, located far 24 km from the mainland, and guards the entrance to the Gulf of Tonkin. It is isolated, but unique in location, and relatively closed to mainland. Despite its small size, the characteristics of morphology and spatial structures, geological composition, area, height, ecological landscape, dynamics and stability of the island... create great values of geo-natural position resources and favorable environment for island residents. Regarding geo - economic position resources, the island is a district under the Quang Tri province, a priority location for development of the country’s marine and island economy, and the economic centre at the entrance of the Gulf of Tonkin. This is also a convenient site for the development of marine economic sectors such as fishery, natural conservation, services - tourism and some others. In terms of geo-political position resources, the island has tremendous advantages for the sovereignty, sovereign rights and national interests at sea. As an outpost at the highly sensitive geo-political area, the Con Co island has the great value of defense, as a solid military base in the entrance of the Gulf of Tonkin and the most important link in the line of defense from coastal islands in the North Centre. It possesses many valuable cultural heritages, especially the heroic relics during the war against the US